All the wild and lonely places : - Hogue, Lawrence (Island Press, 2000)
The book included, perhaps necessarily, quite a bit of information on past and current politics regarding the handling of this unique area. While there were parts of the book that challenged my previous impression of the desert as "untouched" and "pristine" - and made me wonder if I really wanted that impression challenged - ultimately my attraction to the desert became more informed, not spoiled.